Time dependent wave packet treatment of 2ΠgN2− and 3Σ−NO− shape resonances using two‐dimensional surfaces for electron‐N2 and NO interactions. Issue 2 (24th July 2012) - Shandilya, Bhavesh K.; Sarma, Manabendra; Adhikari, Satrajit; Mishra, Manoj K.
Abstract The 2ΠgN 2−<inline-graphic xlink:href="ark:/27927/pgg1q8zmnk2" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" /> and 3Σ−NO− resonances in electron‐N2 and NO collisions have been treated using both nuclear and electronic degrees of freedom and a two‐dimensional (2D) time dependent wave packet approach to ascertain the importance of nonlocality in electron–nuclear interaction. The results so obtained are compared with vibrational excitation cross‐sections obtained experimentally and those from other theoretical/numerical approaches using 1D local complex potential, 2D model with a combination of the exterior complex scaling method and a finite‐element implementation of the discrete‐variable representation. The results obtained provide detailed insight into the nuclear dynamics induced by electron–molecule collision and reveal that while for resonant excitation of lower vibrational modes, the nonlocal effect may not be as critical but importance of nonlocal effects may increase with increase in quanta of resonant vibrational excitation. © 2012 Wiley Periodicals, Inc.